Psychoactive drugs in the Brazilian public health system: Use profile and associated factors - Manuela Roque Siani-Morello; Lucas Borges Pereira; Iahel Manon de Lima Ferreira; Marcela Jirón Aliste; Leonardo Régis Leira Pereira (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract The purpose of this study is to estimate the prevalence of and characterize the use of psychoactive drugs among drug users in a Brazilian municipality, relating the findings to factors associated with the consumption of these substances. Through a cross-sectional design, 1,355 drug users from the public health systems community pharmacies were interviewed. Sociodemographic and health-related data were collected, as well as any other prescribed drugs. The prevalence of psychoactive drug use within the last month was 31.0%, with antidepressants and benzodiazepines being the most prescribed (53.5% and 24.6% respectively). Most psychoactive drug users were female (81.9%), lived with a partner (52.6%), had private health insurance (69.2%) and a monthly per-capita income up to one minimum wage (54.0%). The adjusted Odds Ratio (OR) confirmed the following factors to be positively associated with the use of psychoactive drugs: female gender (OR=2.06; 95% CI 1.44; 2.95), age ≥60 years old (OR=1.77; 95% CI 1.26; 2.48), follow-up with a psychologist (OR=4.12; 95% CI 1.84; 5.25), absence of regular physical activity (OR=1.59; 95% CI 1.13; 2.23), and smokers (OR=1.94; 95% CI 1.26; 2.97). Approximately one out of three individuals used at least one psychoactive drug. Health managers should focus the planning and actions aimed at their rational use for these groups, leading to increased overall treatment success.